EFFECTIVE COMMUNICATION OF THE SBAR METHOD AND PATIENT SAFETY CULTURE OF COMMUNITY HEALTH CENTERS IN SURABAYA - Huda, Nuh; Irawandi, Dedi; Aulisna, Farda (NurseLine Journal, 2026)
Background: Effective communication is a key component for nurses in achieving patient safety in accordance with established standards at health centers. Community Health Centers in Surabaya have implemented a patient safety program to support this goal. Methods: This study aimed to examine the relationship between effective communication using the SBAR method and patient safety culture in community health centers in Surabaya. An analytical descriptive design with a cross-sectional approach was employed. A total of 36 respondents were selected using a probability sampling method, specifically simple random sampling. The study variables included SBAR-based communication and patient safety culture. Data were collected using the SBAR questionnaire and the Hospital Survey on Patient Safety Culture developed by the Agency for Healthcare Research and Quality (AHRQ). Data were analyzed using Spearman’s rho correlation test. Results: The findings showed that 52.8% of respondents practiced moderately effective communication, while 47.2% demonstrated effective communication. In terms of patient safety culture, 63.9% of respondents reported a moderately good level, and 36.1% reported a good level. Conclusion: A significant relationship was identified between effective communication using the SBAR method and patient safety culture in community health centers (ρ = 0.048; r = 0.331). Effective SBAR communication can therefore serve as a strategy to strengthen and improve patient safety culture within health centers. Keywords: Communication; patient safety culture; SBAR